2006
DOI: 10.1100/tsw.2006.25
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D as a Neuroactive Substance: Review

Abstract: The objectives of this paper were (1) to review recent research on the actions of vitamin D as a steroid derivative with neuroactive properties and (2) to highlight clinical relevance and need for more research. Our methods included review of research from current journals, Medline, and Cochrane Reviews; theoretical discussion. Scientific research has had a justifiably strong emphasis on how vitamin D affects calcium metabolism and bone. This appears to have eclipsed its fundamental actions on several other im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
64
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(67 citation statements)
references
References 137 publications
1
64
0
2
Order By: Relevance
“…One study showed that vitamin D potentiates axon regeneration by significantly increasing axogenesis and axon diameter in a rat model of peripheral nerve injury (Chabas et al 2008). Thus vitamin D may have a potential role in the treatment of CNS injuries (Kiraly et al 2006;Cekic et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…One study showed that vitamin D potentiates axon regeneration by significantly increasing axogenesis and axon diameter in a rat model of peripheral nerve injury (Chabas et al 2008). Thus vitamin D may have a potential role in the treatment of CNS injuries (Kiraly et al 2006;Cekic et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…2 In addition, vitamin D exerts antithrombotic and neuroprotective effects and was shown to attenuate ischemic cortical injury in rats. 11,12 We acknowledge that our results may be limited because the z values for vitamin D metabolites were based on data from patients referred to coronary angiography and not from a "healthy" control group. With reference to our work and the meta-analysis that found an increased survival in persons treated with vitamin D, we are of the opinion that it is a promising and safe preventive/therapeutic approach to supplement vitamin D in patients after stroke and at high risk for stroke to maintain 25(OH)D concentrations of at least 75 nmol/L (30 ng/mL), which have been shown to be most effective in producing favorable health outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, people with vitamin D deficiency have higher risk of developing schizophrenia (Kiraly et al, 2006).…”
Section: Discussionmentioning
confidence: 99%